The Influence of Loyalty, Work Discipline, and the Utilization of Information Technology on the Performance of Teaching Staff at the Modern Islamic Boarding School Ummul Quro Al-Islami, Bogor - Hafiddudin, Ahmad Lutfi (Islamic Economic Scholar Association and Faculty of Economics and Business Universitas Jenderal Soedirman, 2025)
The aims of this research is to find out the effect of Loyalty, Work Discipline and Use of Information Technology on the Performance of Teaching Staff. The population of this research is all teaching staff at the Ummul Quro Al-Islami Bogor Modern Islamic Boarding School. The number of respondents taken in this research was 90 teaching staff. The sampling method used is Convenience Sampling. Based on the results of research and quantitative data analysis using the SPSS 20 program that has been carried out, it shows that: 1) 17.6% of the variation in teaching staff performance variables can be explained by the variables Loyalty, Work Discipline and Use of Information Technology; 2) Loyalty and Work Discipline have a significant positive effect on the Performance of Teaching Staff; 3) The use of Information Technology has a positive but not significant effect on the Performance of Teaching Staff; 4) Loyalty, work discipline and use of information technology simultaneously influence the performance of teaching staff; 5) There is a difference in the level of Loyalty between the teaching staff at MTS and MA at the Ummul Quro Al- Islami Bogor Modern Islamic Boarding School. The managerial implications of the conclusions in this study: 1) Pay more attention to the basic needs of the teaching staff and make full efforts to meet them; 2) Provide further awareness regarding the level of absenteeism among teaching staff, and further emphasize the existing rules by providing punishment and rewards for teaching staff who are often absent/late and who are always on time; 3) Further improve Islamic boarding school facilities in terms of developing technology to support the learning process, such as labs which are still minimal and not sufficient for needs and pay more attention to the ability of the teaching staff in using computers or by regularly providing courses or training for students. teaching staff.